Young Mothers as Peer Researchers in a Collaborative Study. Issue 1 (1st March 2023) - Kamusiime, Annah
Abstract: In this article, I draw on experiences of a collaborative ethnographic study conducted with young mothers as peer researchers in a poor urban locale in Kampala-Uganda. Young motherhood has been researched on and about, but not often with women who live the reality of early reproduction. They are frequently left out of the research process as knowledge co-creators and co-interpreters irrespective of the consensus that girls' and women's agency and voice must be acknowledged. I weave together a collaborative approach with polyphony to reveal innovative ways of knowledge co-creation. I call for centering young mothers as people with a specific embodied experience in order to include their perspectives in research, empower them to tell their stories, and question and challenge the dominant discourses.